How is the Muslim Counselor's Experience in Implementing Single-Session Online Counseling on Adolescent? - Mulawarman Mulawarman; Eni Rindi Antika; Shania Dhea Menany Soputan; Putri Nur Aini; Mayang T. Afriwilda; Abi Fa'izzarahman Prabawa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2023)
Effective and efficient counseling service interventions are the goal of every counselor in providing psychological assistance to adolescents. This study aims at describing the Muslim counselors' experience in implementing single-session online counseling services focusing on solutions for adolescents. Before the researchers conducted this study, first of all, they were preparing instruments, and a list of questions, as an interview guide for data collection. After the data collection process, the researchers analyzed and interpreted the data. Data were analyzed using a qualitative approach through thematic analysis. The data were then classified into three sub-themes; Namely creating a safe and comfortable online counseling relationship, basic communication skills in online counseling, and time management in online counseling. The results show that relationship building in online counseling services requires counselors' acceptance, strategy, and self-disclosure. During the online counseling process, counselors need to apply basic counseling skills and specific techniques in solution-focused single-session counseling strategies. They are scaling questions, miracle questions, and exception questions. Time management in the implementation of online counseling is also a challenge for counselors. Flexible time needs to be managed properly so as not to hinder the counseling process.